Drug repositioning: current scenario and future prospective for rewriting saga of drug development - Dixit, Alok; Mishra, Ajit K.; Singh, Chandra Veer; Gupta, Vinay Kumar; Pandey, Devesh (International Journal of Research in Medical Sciences, 2024)
Drug development is a process that demands huge investment of resources and time with only 1 drug candidate successful in reaching market among 10,000 screened taking time duration of 10-15 years and millions of dollars. This high attrition rates discourage investors and researchers. The pharmaceutical industry is shifting its attention away from de novo drug research and towards discovering novel targets and indications for already-approved drugs. In order to accelerate the drug development process with reduced risk of failure and relatively lower costs, pharmaceutical companies have adopted drug repositioning as an alternative. Therefore, a good strategy for drug development would be drug repositioning or drug repurposing, which is to identify, investigate, and exploit new therapeutic uses of already-available, on-market drugs, as well as those that have been withdrawn due to toxicities or that remain on shelves in various stages of development. The outbreak of SARS-COV-19 shows that humanity is constantly vulnerable to epidemics and new microbial attacks and that there is no time to create disease-specific therapies. Consequently, it would seem advantageous to use what is already accessible. Novel therapeutic indications that have previously been approved by the market can reduce investment costs significantly in terms of money, resources, and most importantly, time, as long as they meet PKPD and toxicity standards. Sponsors and pharmaceutical corporations get enthusiastic about additional investments and initiatives related to drug development as a consequence. The upcoming therapeutic revolution, especially with the aid of artificial intelligence, is indicated by the successful applications of several already-available drugs against COVID-19 and the various phases of repurposed drugs against TB, colorectal cancer, Alzheimer’s disease, cervical cancer, and Parkinsonism.